Harold Pinter’s influence to the English literature - A.R.BASHIRZADE (Foundations and Trends in Research, 2025)
Harold Pinter is an English playwright, poet, screenwriter, actor, director and public figure of Jewish origin. For many years he has been the head of the School of Drama and Stage Speech at the University of London. He was born in the British capital into a middle-class family. Three of his grandparents were Polish and one was an Odessa Jew. Although Harold Pinter entered the Royal Academy of Dramatic Art in 1948, he did not complete his education. While still at school, he began to participate in amateur performances. In the early 50s, he showed more inclination towards poetry, and at the same time he became an actor in the Irish theater troupe. His first stage work, the play "Birthday", was performed at the Bristol University Theater in 1957. Three years later, another play called "The Watchman" was staged, and this work earned Pinter the title of the best English playwright of the second half of the 20th century. At that time, the author had just turned 30. His early plays are often called "comedies of menace." Harold Pinter wrote his most popular works in the first half of the 1960s. These include "The Collection" (1961), "Acquaintances" (1962), "The Teahouse" (1964), "Homecoming" (1964) and other plays. Almost all of these plays were successfully staged on the stage of British theaters. In later years, the writer's plays "The Land Without Owners" (1974), "Treason" (1978), "The Language of the Mountains" (1988) attracted more attention. Pinter takes his themes from the lives and everyday lives of ordinary people. However, almost all of these works, which begin without promising any surprises, end with an unusual, unexpected and inexplicable ending. For example, in the play "A Light Pain", a middle-aged intellectual sees a silent match seller near his house. He invites him to his apartment.